Analysis of Total Phenolic Content Of Moringa Oleifera Leaf Extract Using Uv-Vis Spectrophotometer - Marisa; Ines Puspita Sari; Avitra Nawang Sari; Ilma Salsabilla Hidayah; Fitri A; Ria Qadariah Arief; Romyun Alvy Khoiriyah; Funsu Andiarna; Irul Hidayati; Eva Agustina (International Conference on Sustainable Health Promotion, 2025)
Background: Moringa leaves (Moringa oleifera) are known to contain phenolic compounds that act as antioxidants, which can help reduce free radical activity and potentially provide health benefits. Objective: This study aimed to determine the total phenolic content of moringa leaf extract. Methods: Moringa leaf extract was prepared by maceration using methanol as the solvent, and the total phenolic content was determined using a UV-Vis spectrophotometer with gallic acid as the standard. Results: Based on the absorbance measurement at a wavelength of 764 nm, the moringa leaves had a concentration of 188.9 mg/L and a total phenolic content of 18.89 mg GAE/g. Conclusion: Based on this research, the extract of moringa leaves contains phenolic compounds, so it has the potential to act as an antioxidant and is beneficial for health.